2020
DOI: 10.1038/s41598-019-57265-2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human thrombomodulin attenuated sepsis severity in a non-surgical preterm mouse model

Abstract: neonatal sepsis is characterised by dysregulated immune responses. Lipid mediators (LMs) are involved in the regulation of inflammation. Human recombinant thrombomodulin (rhTM), an anticoagulant, has anti-inflammatory effects and might be useful for sepsis treatment. A stock caecal slurry (CS) solution was prepared from adult caeca. To induce sepsis, 1.5 mg/g of CS was administered intraperitoneally to 4 d-old wild-type FVB mouse pups. Saline (Veh-CS) or rhTM (3 or 10 mg/kg; rhTM3-CS or rhTM10-CS) was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…At least three different litters were used for survival experiments to eliminate any litter bias effects. For identification, the back or tail of each pup was labeled using a Sharpie marker as described previously [22]. This study was carried out in accordance with the ARRIVE guidelines and performed as approved by the Kobe University Institutional Animal Care and Use Committee (Protocol P180505).…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…At least three different litters were used for survival experiments to eliminate any litter bias effects. For identification, the back or tail of each pup was labeled using a Sharpie marker as described previously [22]. This study was carried out in accordance with the ARRIVE guidelines and performed as approved by the Kobe University Institutional Animal Care and Use Committee (Protocol P180505).…”
Section: Animalsmentioning
confidence: 99%
“…As described previously [21][22][23], a single stock CS solution was prepared from adult ceca and then stored at −80 • C in 1 mL aliquots until use. For examining bacterial viability, an aliquot of stock CS was thawed at room temperature, and 50 µL was plated onto 1.5% agar containing brain/heart infusion (BHI) broth [23].…”
Section: Cs Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, both UTI and TM have been found to have therapeutic effects on sepsis (Jiang et al 2018;Wu et al 2019;Wang et al 2019;Ashina et al 2020), and more meaningfully, a number of studies have shown that UTI combined with other drugs can effectively improve the treatment effect of sepsis (Meng et al 2020;Wang et al 2020). At present, there are many research projects on sepsis, but the research based on drug combination therapy is not su cient.…”
Section: Introductionmentioning
confidence: 98%